MODERNIZATION OF ISLAMIC EDUCATION CURRICULUM: BALANCING TRADITION AND INNOVATION FOR FUTURE GENERATIONS - Khovi, Noqti Nuril; Alfaridli, Muhammad Alfi; Hamzah, Muh (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Abstract:This research aims to analyze the efforts to modernize the Islamic education curriculum in the context of balancing the values of tradition and the demands of innovation. The research method in this study uses literature study. This research examines various literatures related to aspects of curriculum modernization, the importance of balancing tradition and innovation in Islamic education, the challenges faced, and the strategies that can be applied. The results showed that the modernization of the Islamic education curriculum is a necessity in facing the dynamics of the times. However, in the process of modernization, it is important to stick to the fundamental values of Islam and accommodate the diversity of interpretations. This study concludes that the key to successful curriculum modernization lies in the ability to integrate traditional values with the latest innovations, so as to produce graduates who are not only religious, but also competent and relevant to the demands of the times.